Transthyretin cardiac amyloidosis in continental Western Europe: an insight through the Transthyretin Amyloidosis Outcomes Survey (THAOS) - Damy, Thibaud; Kristen, Arnt; Suhr, Ole B.; Maurer, Mathew S.; Planté-Bordeneuve, Violaine; Yu, Ching-Ray; Ong, Moh-Lim; Coelho, Teresa; Rapezzi, Claudio (European heart journal, 2022)
AbstractAims. Transthyretin amyloidosis (ATTR amyloidosis) is a heterogeneous disorder with cardiac, neurologic, and mixed phenotypes. We describe the phenotyp